QTL mapping for early root and shoot vigor of upland rice (Oryza sativa L.) under P deficient field conditions in Japan and Madagascar - Ranaivo, Harisoa Nicole; Lam, Dinh Thi; Ueda, Yoshiaki; Pariasca Tanaka, Juan; Takanashi, Hideki; Ramanankaja, Landiarimisa; Razafimbelo, Tantely; Wissuwa, Matthias (Frontiers in Plant Science, 2022)
Upland rice production is limited by the low phosphorus (P) availability of many highly weathered tropical soils and P deficiency is likely to become increasingly limiting in future drier climates because P mobility decreases sharply with soil moisture. Good seedling root development will be crucial to cope with the combined effects of low P and water availability. Upland rice genebank accession DJ123 was used as a donor for P efficiency and root vigor traits in a cross with inefficient local variety Nerica4 and a set of backcross lines were used to characterize the seedling stage response of upland rice to low P availability and to identify associated QTL in field trials in Japan and Madagascar. Eleven QTL were detected for crown root number, root, shoot and total dry weight per plant in a highly P deficient field in Japan using the BC1F3 generation. Of these, qPef9 on chromosome 9 affected multiple traits, increasing root number, root weight and total biomass, whereas a neighboring QTL on chromosome 9 (qPef9-2) increased shoot biomass. Field trials with derived BC1F5 lines in a low-P field in Madagascar confirmed a highly influential region on chromosome 9, however, qPef9-2 appeared more influential than qPef9, as the shoot and root biomass contrast between lines carrying DJ123 or Nerica4 alleles at qPef9-2 was +33% and +23% compared to +23% and +18% at qPef9. This advantage increased further during the growing season, leading to 46% higher shoot biomass at the late vegetative stage. Results suggest an introgression between 8.0 and 12.9 Mb on chromosome 9 from P efficient donor DJ123 can improve plant performance under P-limited conditions. The QTL identified here has practical relevance because it was confirmed in the target genetic background of the local variety Nerica4 and can therefore be applied directly to improve its performance.